Immunotherapeutic Strategies for Canine Lymphoma: Changing the Odds Against Non-Hodgkin Lymphoma - Dias, Joana N. R.; André, Ana S.; Aguiar, Sandra I.; Gil, Solange; Tavares, Luís; Aires-da-Silva, Frederico (Frontiers in Veterinary Science, 2021)
The new era of immune-oncology has brought complexities and challenges that emphasize the need to identify new strategies and models to develop successful and cost-effective therapies. The inclusion of a canine model in the drug development of cancer immunotherapies is being widely recognized as a valid solution to overcome several hurdles associated with conventional preclinical models. Driven by the success of immunotherapies in the treatment of human non-Hodgkin lymphoma (NHL) and by the remarkable similarities of canine NHL to its human counterpart, canine NHL has been one of the main focus of comparative research. Under the present review, we summarize a general overview of the challenges and prospects of today’s cancer immunotherapies and the role that comparative medicine might play in solving the limitations brought by this rapidly expanding field. The state of art of both human and canine NHL and the rationale behind the use of the canine model to bridge the translational gap between murine preclinical studies and human clinical trials are addressed. Finally, a review of currently available immunotherapies for canine NHL is described, highlighting the potential of these therapeutic options.